2013
DOI: 10.1080/15567036.2011.582616
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biodiesel and Its Blends with an Oxygenated Additive on the Combustion, Performance, and Emissions from a Diesel Engine

Abstract: An experimental investigation has been carried out to evaluate the effect of using diethyl ether as an additive to biodiesel on the combustion, performance, and emission characteristics in an unmodified diesel engine at different loads and constant engine speed. The results indicate that peak cylinder pressure and heat release rate is higher for 5% (by vol.) diethyl ether blended biodiesel than those of neat biodiesel. The carbon monoxide and smoke emissions decrease while oxides of nitrogen and hydrocarbon em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Because neem oil has a good amount of such FAs in the form of oleic acid, it is expected that the quality of biodiesel or fatty acid methyl esters (FAME) obtainable from it would have desired fuel properties in terms of cetane number and viscosity. , Also, a good oxidative stability is expected from it by virtue of the relatively low amount of polyunsaturated fatty acids (linoleic and linolenic) in it as compared to rapeseed and soybean oils . These differences in FA contents in neem oil and widely studied rapeseed and soybean oils have motivated several combustion studies on biodiesel from neem oil. , For example, some recent experimental studies in diesel engines fueled with neem oil-derived biodiesel/diesel blends report an enhancement in brake thermal efficiency and a reduction in soot, CO, and unburnt hydrocarbon emissions, as compared to pure diesel, though NO x emission increases. ,,, However, no studies on the characteristics of soot produced from neem-derived biodiesel could be found in the literature. Moreover, while there is sufficient evidence in the literature that blending biodiesel with diesel has a substantial effect on reducing soot emissions from diesel engines and on the reduction of primary particle size in soots, their effects on the soot characteristics are still less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Because neem oil has a good amount of such FAs in the form of oleic acid, it is expected that the quality of biodiesel or fatty acid methyl esters (FAME) obtainable from it would have desired fuel properties in terms of cetane number and viscosity. , Also, a good oxidative stability is expected from it by virtue of the relatively low amount of polyunsaturated fatty acids (linoleic and linolenic) in it as compared to rapeseed and soybean oils . These differences in FA contents in neem oil and widely studied rapeseed and soybean oils have motivated several combustion studies on biodiesel from neem oil. , For example, some recent experimental studies in diesel engines fueled with neem oil-derived biodiesel/diesel blends report an enhancement in brake thermal efficiency and a reduction in soot, CO, and unburnt hydrocarbon emissions, as compared to pure diesel, though NO x emission increases. ,,, However, no studies on the characteristics of soot produced from neem-derived biodiesel could be found in the literature. Moreover, while there is sufficient evidence in the literature that blending biodiesel with diesel has a substantial effect on reducing soot emissions from diesel engines and on the reduction of primary particle size in soots, their effects on the soot characteristics are still less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Just as with brakespecific fuel consumption and power, blends of biodiesels can also alter the NOx emissions. CO is one of the consequences of incomplete fuel combustion ( [9] and [22]). Concentration of oxygen during combustion enhances the oxidation rate of CO and leads to less CO formation.…”
mentioning
confidence: 99%
“…From which it is to be noted that the NO X emissions are lower for ES biodiesel blends B10, B20 and B30 when compared to base diesel. This NO X emission reduction can be attributed to lower combustion temperature caused by the blends lower heat release rate and which may be due to the poor blend and air mixing [45]. NO X emissions reduced on an average by 12.70%, 2.31% and 6.18% for blends B10, B20 and B30 respectively compared to diesel.…”
Section: Nitrogen Oxide Emissionmentioning
confidence: 96%